An Investigation of the Hedging Behaviour and Characteristics of U.S. And EX-U.S. Airlines - Mistry, Shailen (2017)
This paper looks at the hedging behaviour and characteristics of U.S. airlines and EX-U.S. airlines with the aim of making meaningful comparisons and observations between them. This paper utilises a sample of 61 airlines (8 U.S. airlines and 53 EX-U.S. airlines) across 37 countries over a period of 14 years (2002-2015). The methodology incorporates a number of tests which include: means difference tests, univariate logit tests and multivariate logit tests. The results of these tests provided overpowering evidence in support of H1, that larger firms hedge more. This is in line with theories that indicate economies of scale and transaction cost scale economies leading to increased hedging. The results measuring financial distress costs provide some conflicting views. For EX-U.S. airlines, interest coverage provided to be significant and consistent with the hypothesis that the higher the expected costs of financial distress the more likely an airline is to hedge. For U.S. airlines the results were insignificant. When using measures of leverage, they provided significant and meaningful results in accordance with the hypothesis for U.S. airlines but a significant and negative relationship for EX-U.S. airlines. The fuel expense variable yields significant and meaningful results for the U.S. sample in accordance with the hypothesis that the more exposed an airline is to fuel risk the more likely it is to hedge its fuel risk. However, EX-U.S. airlines yield insignificant and inconsistent views with the same hypothesis. This leads to the belief that EX-U.S. airlines view hedging to be insignificant upon total costs. This is somewhat surprising considering that they have higher average fuel costs as a percentage of total operating costs, as can be seen in Figure 1.